Exterior materials for power storage devices
Patent Information
- Application Number
- JP2023135404
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2036-10-31
AI Technical Summary
【0023】 [1]の発明では、シーラント層の最内層が、共重合成分としてプロピレン及びプロピレンを除く他の共重合成分を含有するランダム共重合体と、粗面化材と、滑剤と、を含有し、粗面化材は、熱可塑性樹脂を含有する粒子からなり、最内層の表面の中心線平均粗さRaが0.05μm~1μmであるから、成形時に良好なすべり性を確保できて成形性に優れる。更に、滑剤とともに粗面化材を併用することにより(粗面化材の併用により従来よりも滑剤使用量を少なくできることにより)最内層の表面の中心線平均粗さRaを0.05μm~1μmに設定しているので、外装材のシーラント層の最内層の表面7aに白粉が表出し難い。このように白粉が表出し難いので、外装材の生産性を向上させることができると共に、シーラント層同士をヒートシールした後の該ヒートシール部において十分な密封性を確保できる。また、このように粗面化材の併用により従来よりも滑剤使用量を少なくできることにより、例えばエージング工程を行う場合において滑剤のブリードアウト量の調整を行う必要がなくなり、エージング工程を不要にしたり、或いはエージング工程を短時間で済ませることが可能になるので、外装材の生産性を一層向上させることができる。また、粗面化材は、熱可塑性樹脂を含有する粒子からなるので、最内層用樹脂の加工時にフィルターが目詰まりすることを低減でき、生産性をより一層向上させることができる。更に、粗面化材は、熱可塑性樹脂を含有する粒子からなるので、シリカ粒子のように外から加圧した際に内部にめり込んだり、脱落するようなことがない。
Smart Images

Figure 0007635320000005 
Figure 0007635320000006 
Figure 0007635320000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an exterior material for electricity storage devices such as batteries and capacitors used in portable devices such as smartphones and tablets, and batteries and capacitors used for storing electricity in hybrid automobiles, electric automobiles, wind power generation, solar power generation, and night-time electricity, and to an electricity storage device exteriorly packaged with the exterior material.
[0002] In the claims and the specification of the present application, the term "center line average roughness (Ra)" means the center line average roughness (Ra) measured in accordance with JIS B0601-2001.
[0003] In the claims and specification of the present application, the term "density" refers to a density measured in accordance with JIS K7112-1999 Method D (density gradient tube method).
[0004] In addition, in the claims and specification of the present application, the term "melt flow rate (MFR)" means a melt flow rate measured in accordance with JIS K7210-1-2014.
[0005] In addition, in the present specification, the term "swell (percent)" refers to the room temperature die swell percentage (%) measured by the Capillary Rheometer A method defined in JIS K7199-1999. [Background technology]
[0006] In recent years, as mobile electrical devices such as smartphones and tablet terminals become thinner and lighter, a laminate consisting of a heat-resistant resin layer / adhesive layer / metal foil layer / adhesive layer / thermoplastic resin layer (inner sealant layer) is used as the exterior material of the electricity storage devices such as lithium ion secondary batteries, lithium polymer secondary batteries, lithium ion capacitors, and electric double layer capacitors mounted thereon, instead of the conventional metal can. In addition, power sources for electric vehicles and the like, large power sources for electricity storage, capacitors, etc. are increasingly being exteriorized with the laminate (exterior material) having the above configuration. The laminate is molded into a three-dimensional shape such as a substantially rectangular parallelepiped shape by performing stretch molding or deep drawing. By molding into such a three-dimensional shape, it is possible to secure a storage space for accommodating the main body of the electricity storage device.
[0007] Improving the slipperiness of the surface of the inner sealant layer is required to form such a three-dimensional shape in a good condition without pinholes, breaks, etc. As a laminate material for secondary battery containers that improves the slipperiness of the surface of the inner sealant layer to ensure good formability, a laminate material has been proposed in which an exterior resin film, a first adhesive layer, a chemically treated aluminum foil, a second adhesive layer, and a sealant film are laminated in this order, the sealant film being made of a random copolymer of propylene and an α-olefin with an α-olefin content of 2 to 10% by weight, and containing 1000 to 5000 ppm of a lubricant (see Patent Document 1). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2003-288865 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, in the above-mentioned conventional technology, it is difficult to control the amount of surface lubricant precipitation depending on the heating and holding time and storage period in the production process of the exterior material (laminate material), and although the slipperiness during molding is good, the lubricant is excessively precipitated on the surface, so that the lubricant adheres to and accumulates on the molding surface of the molding die during molding of the exterior material, generating white powder (white powder caused by the lubricant). When such white powder adheres to and accumulates on the molding surface, it becomes difficult to perform good molding, so it becomes necessary to clean and remove the white powder every time it adheres and accumulates, but there is a problem that cleaning and removing such white powder reduces the productivity of the exterior material.
[0010] Of course, if the amount of lubricant added (lubricant content) is reduced, it is possible to suppress the adhesion and accumulation of white powder, but in this case, the amount of lubricant deposited on the surface is insufficient, which causes a problem of poor moldability. Thus, in the past, it was difficult to achieve both excellent moldability and suppression of the appearance of white powder on the surface of the exterior material.
[0011] The present invention has been made in consideration of this technical background, and has an object to provide an exterior material for an electricity storage device, an exterior case for an electricity storage device, and an electricity storage device that ensure good slip properties during molding, have excellent moldability, and are less likely to produce white powder on the surface. [Means for solving the problem]
[0012] In order to achieve the above object, the present invention provides the following means.
[0013] [1] An exterior material for an electricity storage device, comprising a heat-resistant resin layer as an outer layer, a sealant layer as an inner layer, and a metal foil layer disposed between these layers, The sealant layer is composed of one or more layers, and the innermost layer of the sealant layer contains a random copolymer containing propylene and other copolymer components excluding propylene as copolymer components, a surface-roughening material, and a lubricant; The surface roughening material is made of particles containing a thermoplastic resin, The outer casing material for an electricity storage device, wherein the center line average roughness Ra of the surface of the innermost layer is 0.05 μm to 1 μm.
[0014] [2] The exterior material for a storage battery device according to the preceding paragraph 1, wherein the thermoplastic resin constituting the surface-roughening material is a high-density polyethylene resin.
[0015] [3] The density of the high-density polyethylene resin is 0.935 g / cm 3 ~0.965g / cm 3 3. An exterior material for an electricity storage device according to item 2 above, wherein the high-density polyethylene resin has a melt flow rate at 190° C. in the range of 0.01 g / 10 min to 2 g / 10 min.
[0016] [4] The exterior material for an electricity storage device according to any one of items 1 to 3, wherein the content of the surface roughening material in the innermost layer of the sealant layer is 1% by mass to 30% by mass, and the content of the lubricant in the innermost layer is more than 0 ppm and 1,000 ppm or less.
[0017] [5] The exterior material for an electricity storage device according to any one of items 1 to 4 above, wherein the lubricant is one or more lubricants selected from the group consisting of fatty acid amides, waxes, silicones, and paraffins.
[0018] [6] The exterior material for an electricity storage device according to any one of items 1 to 5 above, wherein the sealant layer is made of a plurality of layers.
[0019] [7] The sealant layer includes the innermost layer and a first intermediate layer laminated on a surface of the innermost layer facing the metal foil layer, The first intermediate layer contains an elastomer-modified olefin resin, The elastomer-modified olefin-based resin comprises an elastomer-modified homopolypropylene and / or an elastomer-modified random copolymer, 7. The exterior material for an electricity storage device according to item 6 above, wherein the elastomer-modified random copolymer is an elastomer-modified random copolymer containing, as copolymerization components, propylene and a copolymerization component other than propylene.
[0020] [8] The sealant layer includes the innermost layer, a first intermediate layer laminated on a surface of the innermost layer facing the metal foil layer, and a second intermediate layer laminated on a surface of the first intermediate layer facing the metal foil layer, The first intermediate layer contains an elastomer-modified olefin resin, The elastomer-modified olefin-based resin comprises an elastomer-modified homopolypropylene and / or an elastomer-modified random copolymer, The elastomer-modified random copolymer is an elastomer-modified random copolymer containing propylene and other copolymer components other than propylene as copolymer components, 7. The exterior packaging material for an electricity storage device according to item 6 above, wherein the second intermediate layer contains a random copolymer containing, as a copolymerization component, propylene and a copolymerization component other than propylene.
[0021] [9] An exterior case for an electricity storage device, comprising a molded article of the exterior material for an electricity storage device according to any one of items 1 to 8 above.
[0022]
[10] A main body of an electricity storage device; an exterior member made of the exterior material for an electricity storage device according to any one of items 1 to 8 above and / or the exterior case for an electricity storage device according to item 9 above, The power storage device, wherein the power storage device main body is exteriorly covered with the exterior member. Effect of the Invention
[0023] In the invention of [1], the innermost layer of the sealant layer contains a random copolymer containing propylene and other copolymer components except propylene as copolymer components, a surface-roughening material, and a lubricant, and the surface-roughening material is made of particles containing a thermoplastic resin, and the center line average roughness Ra of the surface of the innermost layer is 0.05 μm to 1 μm, so that good slipperiness can be ensured during molding and excellent moldability. Furthermore, by using the surface-roughening material in combination with the lubricant (by using the surface-roughening material in combination, the amount of lubricant used can be reduced compared to the conventional method), the center line average roughness Ra of the surface of the innermost layer is set to 0.05 μm to 1 μm, so that white powder is unlikely to appear on the surface 7a of the innermost layer of the sealant layer of the exterior material. Since white powder is unlikely to appear, the productivity of the exterior material can be improved, and sufficient sealing can be ensured at the heat-sealed portion after the sealant layers are heat-sealed to each other. In addition, by using the surface-roughening material in combination, the amount of lubricant used can be reduced compared to the conventional method, and therefore, for example, when performing an aging process, it is not necessary to adjust the amount of lubricant bleed-out, and the aging process can be eliminated or completed in a short time, which can further improve the productivity of the exterior material. In addition, since the surface-roughening material is made of particles containing a thermoplastic resin, clogging of the filter during processing of the resin for the innermost layer can be reduced, and productivity can be further improved. Furthermore, since the surface-roughening material is made of particles containing a thermoplastic resin, it does not sink into the inside or fall off when pressure is applied from the outside, unlike silica particles.
[0024] In the invention [2], the thermoplastic resin constituting the roughening material is a high-density polyethylene resin, and since the compatibility of the high-density polyethylene resin with the random copolymer is appropriately low, the surface can be effectively roughened and the slipperiness can be further improved.
[0025] In the invention [3], the slipperiness during molding can be further improved, and moldability can be further improved.
[0026] In the invention [4], by setting the content of the surface-roughening material in the innermost layer to 1% by mass to 30% by mass, excellent moldability can be ensured even if the content of the lubricant in the innermost layer is 1000 ppm or less. In addition, since the content of the lubricant in the innermost layer is more than 0 ppm and less than 1000 ppm, white powder is further unlikely to appear on the surface of the innermost layer of the sealant layer of the exterior material. Furthermore, since the content of the lubricant in the innermost layer is more than 0 ppm and less than 1000 ppm, the amount of lubricant present on the surface of the innermost layer of the exterior material can be stabilized even during storage (for example, fluctuations in the amount of lubricant present on the surface of the innermost layer due to long-term storage can be suppressed), and stable and excellent moldability can be ensured.
[0027] In the invention [5], one or more lubricants selected from the group consisting of fatty acid amides, waxes, silicones and paraffins are used as the lubricant, so that better slip properties can be ensured during molding, and thus better moldability can be ensured.
[0028] In the invention [6], the sealant layer is composed of multiple layers, and by configuring one or more layers to be laminated on the surface of the innermost layer facing the metal foil layer, it is possible, for example, to further improve the adhesive strength between the sealant layer and the metal foil layer.
[0029] In the invention [7], the sealant layer includes an innermost layer and a first intermediate layer of the specific configuration laminated on the surface of the innermost layer facing the metal foil layer. This makes it possible to sufficiently suppress whitening of the sealant layer during molding and to sufficiently ensure sealing performance when heat-sealed.
[0030] In the invention [8], the sealant layer includes an innermost layer, a first intermediate layer of the specific configuration laminated on the metal foil layer side of the innermost layer, and a second intermediate layer of the specific configuration laminated on the metal foil layer side of the first intermediate layer. Therefore, in addition to being able to enjoy the effects of the invention [7], the adhesive strength between the sealant layer and the metal foil layer can be further improved and sufficient insulation can be ensured.
[0031] The invention [9] can provide an outer casing for an electricity storage device that is well molded and that is less likely to produce white powder on the surface of the outer casing (the surface of the innermost layer of the sealant layer).
[0032] The invention of
[10] provides an electricity storage device that is packaged with an exterior material for electricity storage devices and / or an exterior case that is well molded and that is less likely to produce white powder on the surface (the surface of the innermost layer of the sealant layer). [Brief description of the drawings]
[0033] [Figure 1] 1 is a cross-sectional view showing a first embodiment of an exterior material for an electricity storage device according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a second embodiment of an exterior material for an electricity storage device according to the present invention. [Diagram 3] FIG. 4 is a cross-sectional view showing a third embodiment of an exterior material for an electricity storage device according to the present invention. [Figure 4] 1 is a cross-sectional view showing one embodiment of an electricity storage device according to the present invention. [Diagram 5] FIG. 5 is a perspective view showing an exterior material (flat), an electricity storage device main body, and an exterior case (a molded body molded into a three-dimensional shape) constituting the electricity storage device in FIG. 4 in a separated state before being heat-sealed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] The exterior packaging material 1 for an electricity storage device according to the present invention includes a heat-resistant resin layer 2 as an outer layer, a sealant layer 3 as an inner layer, and a metal foil layer 4 arranged between these two layers, the sealant layer 3 being composed of one or more layers, the innermost layer 7 of the sealant layer 3 containing a random copolymer containing propylene and other copolymer components excluding propylene as copolymer components, a surface-roughening material, and a lubricant, the surface-roughening material being composed of particles containing a thermoplastic resin, and the center line average roughness Ra of a surface 7a of the innermost layer 7 is 0.05 μm to 1 μm.
[0035] Three embodiments of the exterior packaging material 1 for an electricity storage device according to the present invention are shown in Figures 1 to 3. These three embodiments are merely representative embodiments, and the present invention is not particularly limited to these configurations.
[0036] Each of the exterior packaging materials 1 for an electricity storage device shown in Figures 1 to 3 has a configuration in which a heat-resistant resin layer (outer layer) 2 is laminated integrally to one surface (upper surface) of a metal foil layer 4 via a second adhesive layer (outer adhesive layer) 5, and a sealant layer (inner layer) 3 is laminated integrally to the other surface (lower surface) of the metal foil layer 4 via a first adhesive layer (inner adhesive layer) 6.
[0037] In the exterior packaging material 1 for an electricity storage device shown in Fig. 1, the sealant layer (inner layer) 3 is composed of the innermost layer 7 and a first intermediate layer 8 laminated on the surface of the innermost layer 7 facing the metal foil layer 4. That is, the first intermediate layer 8 is laminated on the other surface (lower surface) of the metal foil layer 4 via a first adhesive layer (inner adhesive layer) 6, and the innermost layer 7 is laminated on the surface (lower surface) of the first intermediate layer 8. The innermost layer 7 is exposed to the inside surface of the exterior packaging material 1 (see Fig. 1).
[0038] In the exterior packaging material 1 for an electricity storage device shown in Fig. 2, the sealant layer (inner layer) 3 is composed of the innermost layer 7, a first intermediate layer 8 laminated on the surface of the innermost layer 7 facing the metal foil layer 4, and a second intermediate layer 9 laminated on the surface of the first intermediate layer 8 facing the metal foil layer 4. That is, the second intermediate layer 9 is laminated on the other surface (lower surface) of the metal foil layer 4 via a first adhesive layer (inner adhesive layer) 6, the first intermediate layer 8 is laminated on the surface (lower surface) of the second intermediate layer 9, and the innermost layer 7 is laminated on the surface (lower surface) of the first intermediate layer 8. The innermost layer 7 is exposed to the inner surface of the exterior packaging material 1 (see Fig. 2).
[0039] In the exterior packaging material 1 for an electricity storage device shown in Fig. 3, the sealant layer (inner layer) 3 is made of the innermost layer 7. That is, the sealant layer 3 made of the innermost layer 7 is laminated on the other surface (lower surface) of the metal foil layer 4 via a first adhesive layer (inner adhesive layer) 6. The innermost layer 7 is exposed on the inner surface of the exterior packaging material 1 (see Fig. 3).
[0040] In the present invention, the sealant layer (inner layer) 3 has the function of providing excellent chemical resistance against highly corrosive electrolytes used in lithium ion secondary batteries and the like, and also of imparting heat sealability to the exterior material.
[0041] In the present invention, the innermost layer 7 of the sealant layer 3 contains a random copolymer containing propylene and other copolymer components except propylene as copolymer components, a surface roughening material, and a lubricant.
[0042] The random copolymer contains "propylene" and "other copolymer components other than propylene" as copolymer components. Regarding the random copolymer, the "other copolymer components other than propylene" are not particularly limited, but examples thereof include olefin components such as ethylene, 1-butene, 1-hexene, 1-pentene, and 4-methyl-1-pentene, as well as butadiene.
[0043] The random copolymer (a random copolymer containing propylene and other copolymer components other than propylene as copolymerization components) preferably has a melt flow rate (MFR) at 230°C in the range of 1g / 10 min to 10g / 10 min. By using the random copolymer having an MFR in the range of 1g / 10 min to 10g / 10 min, the roughening material can be finely and uniformly dispersed, and the sealing property when sealing the main body of the electric storage device in the exterior material is improved to obtain sufficient heat seal strength, and the reduction in the thickness of the sealant layer after heat sealing can be suppressed, thereby further improving the insulation. When an ethylene-propylene random copolymer is used as the random copolymer, the ethylene content in the random copolymer is preferably 3% by mass to 7% by mass, and in this case, high heat seal strength can be obtained even when heat sealing is performed at a relatively low heat seal temperature of about 200°C. In addition, the melting point of the random copolymer is preferably in the range of 140°C to 155°C.
[0044] The surface-roughening material is not particularly limited, but for example, a thermoplastic resin-containing pellet, a thermoplastic resin-containing powder, etc. are used. Among these, a thermoplastic resin-containing powder is preferable in terms of dispersibility. The thermoplastic resin constituting the surface-roughening material is not particularly limited, but for example, a high-density polyethylene resin, a low-density polyethylene resin, an ethylene-olefin (olefin other than ethylene) copolymer resin, an ethylene-vinyl ester copolymer resin, a polystyrene resin, etc. are mentioned. Among them, it is preferable to use a surface-roughening material containing a high-density polyethylene resin as the surface-roughening material, and in this case, the surface 7a of the innermost layer 7 of the sealant layer can be effectively roughened without impairing the heat sealability, and the slipperiness can be further improved.
[0045] The surface-roughening material particles, which have low compatibility with the matrix of the random copolymer constituting the innermost layer 7, are dispersed in the matrix, and the surface-roughening material particles are partially exposed (protruding) on the surface 7a of the innermost layer 7, forming unevenness on the surface 7a (the surface is roughened). For example, the random copolymer pellets or powder is mixed with thermoplastic resin pellets or thermoplastic resin powder as the surface-roughening material, and the mixture is melt-kneaded in an extruder or the like to finely disperse the mixture, and then cooled and solidified to obtain the surface 7a of the innermost layer 7 having unevenness (the surface is roughened).
[0046] The average particle size of the surface-roughening material in a dispersed state is preferably within a range of 0.05 μm to 10 μm, in which case the slipperiness can be further improved.
[0047] The density of the high density polyethylene resin (HDPE) constituting the roughening material is 0.935 g / cm 3 ~0.965g / cm 3In the case of the density range, the slipperiness can be further improved, and the moldability can be further improved. In particular, the density of the high density polyethylene resin (HDPE) constituting the surface roughening material is preferably in the range of 0.945 g / cm. 3 ~0.960g / cm 3 It is more preferable that the range is .
[0048] The density of the high-density polyethylene resin can be adjusted by changing the content of a comonomer (copolymerization component). Examples of such comonomers include unsaturated olefins other than ethylene, such as 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene, but are not limited thereto. As the comonomer, it is preferable to use at least one comonomer selected from the group consisting of 1-butene and 1-hexene.
[0049] The melt flow rate (MFR) of the high-density polyethylene resin constituting the surface-roughening material at 190°C is preferably in the range of 0.01g / 10min to 2g / 10min. By having an MFR of "0.01g / 10min" or more, the surface-roughening material can be finely and uniformly dispersed in the random copolymer, and by having an MFR of "2g / 10min" or less, the surface roughness can be increased, and the slipperiness can be further improved. Among them, it is particularly preferable that the melt flow rate (MFR) of the high-density polyethylene resin (HDPE) constituting the surface-roughening material at 190°C is in the range of 0.1g / 10min to 1g / 10min.
[0050] The melt flow rate (MFR) of the high-density polyethylene resin can be adjusted, for example, as follows. In the case where the high-density polyethylene resin is produced using a Phillips catalyst, the MFR of the high-density polyethylene resin can be adjusted by changing the reactor temperature during polymerization, or the MFR of the high-density polyethylene resin can be adjusted by adding a small amount of hydrogen and then changing the reactor temperature. In the case where the high-density polyethylene resin is produced using a Ziegler catalyst, the MFR of the high-density polyethylene resin can be adjusted by changing the amount of hydrogen supplied to the reactor during polymerization. When the Phillips catalyst is used, the high-density polyethylene resin can be produced by slurry polymerization using isobutane as a solvent, but the method is not particularly limited to this.
[0051] The melting point of the high-density polyethylene resin constituting the surface-roughening material is preferably in the range of 130° C. to 145° C. The high-density polyethylene resin preferably has a long-chain (10 or more carbon atoms) branch. When a high-density polyethylene resin having a long-chain branch is used, surface-roughening material particles are easily formed when the surface-roughening material is melt-kneaded with the random copolymer, so that the surface 7a of the innermost layer can be more effectively roughened and the slipperiness can be further improved.
[0052] The swell of the high-density polyethylene resin constituting the surface-roughening material is preferably in the range of 25% to 55%, and in this case, since the melt viscoelasticity of the resin constituting the surface-roughening material is relatively high, particles of the high-density polyethylene resin are easily formed, and the surface 7a of the innermost layer can be more effectively roughened, and the slipperiness can be further improved. Among them, the swell of the high-density polyethylene resin constituting the surface-roughening material is more preferably in the range of 35% to 45%.
[0053] The above "swell" refers to the room temperature die swell percentage (%) measured by the Capillary Rheometer A method specified in JIS K7199-1999, and is measured by using a standard die (hole diameter: 2.095 mm, length: 8 mm) specified in JIS K7210-1-2014 at a temperature of 190°C and a load of 2.16 kg, and when the strand (string-like resin) of resin extruded from the capillary die reaches a length of 2 cm, the strand is collected with tweezers, and after natural cooling and solidification, the diameter of the strand 1 cm from the tip is measured with a micrometer, and this measurement value is taken as D1 (mm). Swell(%)={(D1-D0) / D0)}×100 D1: diameter of extruded resin D0: Standard die hole diameter (2.095mm) This is the value (%) calculated using the above formula.
[0054] The high load swell (swell at a load of 21.6 kg) of the high density polyethylene resin constituting the roughening material is preferably in the range of 55% to 90%. In this case, since the melt viscoelasticity of the resin constituting the roughening material is relatively high, particles of the high density polyethylene resin are easily formed, and the surface 7a of the innermost layer can be roughened more effectively, further improving the slipperiness.
[0055] The high load swell is measured in accordance with JIS K7199-1999 using a standard die (hole diameter: 2.095 mm, length: 8 mm) specified in JIS K7210-1-2014, at a temperature of 190°C and a load of 21.6 kg. When the strand (string-like resin) of resin extruded from the capillary die reaches a length of 2 cm, the strand is collected with tweezers, and after natural cooling and solidification, the diameter of the strand 1 cm from the tip is measured with a micrometer. When this measured value is taken as D2 (mm), High load swell (%) = {(D2-D0) / D0)} x 100 D2: Diameter of extruded resin D0: Standard die hole diameter (2.095mm) This is the value calculated using the above formula.
[0056] The "high load MFR (MFR at a load of 21.6 kg) / MFR (MFR at a load of 2.16 kg)" of the high-density polyethylene resin constituting the roughening material is preferably in the range of 25 to 40. In this case, compatibility between the random copolymer and the roughening material can be ensured to a certain extent, and whitening of the sealant layer 3 during molding can be further suppressed.
[0057] The difference between the melt density of the surface-roughening material and the density of the surface-roughening material is 0.15 g / cm 3 ~0.25g / cm 3 In this case, the volumetric shrinkage rate of the roughening material increases as the mixed resin cools and solidifies from a molten state, so that the surface 7a of the innermost layer 7 can be efficiently roughened and the center line average roughness Ra of the surface 7a of the innermost layer 7 can be easily adjusted to 0.05 μm to 1 μm.
[0058] In the innermost layer 7 of the sealant layer, the difference between the density of the random copolymer (a random copolymer containing propylene and other copolymer components other than propylene as copolymer components) and the density of the surface roughening material is 0.04 g / cm 3 ~0.07g / cm 3 In this case, the difference in the volume shrinkage rate between the random copolymer and the surface-roughening material becomes large as the mixed resin in the molten state cools and solidifies, so that the unevenness of the surface 7a of the innermost layer becomes large, and the surface 7a of the innermost layer can be roughened more effectively, thereby further improving the slipperiness.
[0059] The difference between the melt density of the random copolymer (a random copolymer containing propylene and other copolymer components other than propylene as copolymer components) and the melt density of the surface-roughening material is 0.3 g / cm 3 It is preferable that:
[0060] The content of the surface-roughening material in the innermost layer 7 of the sealant layer is preferably set to 1% by mass to 30% by mass, and in this case, excellent moldability can be ensured even if the content of the lubricant in the innermost layer 7 is 1000 ppm or less. Furthermore, by setting the content of the lubricant in the innermost layer 7 to more than 0 ppm and not more than 1000 ppm in this manner, it becomes even more difficult for white powder to appear on the surface 7a of the innermost layer 7 of the sealant layer of the exterior material. In particular, the content of the surface-roughening material in the innermost layer 7 of the sealant layer is preferably set to 1% by mass to 20% by mass. Furthermore, the content of the lubricant in the innermost layer 7 is preferably set to more than 0 ppm and not more than 900 ppm, and more preferably set to 10 ppm to 600 ppm.
[0061] The lubricant is not particularly limited, but it is preferable to use one or more lubricants selected from the group consisting of fatty acid amides, waxes, silicones, and paraffins. Among them, it is particularly preferable to use fatty acid amides as the lubricant. The fatty acid amide is not particularly limited, but examples thereof include erucic acid amide, behenic acid amide, etc.
[0062] In the present invention, an antiblocking agent may be contained in the innermost layer 7 as long as the effect of the present invention is not impaired (see Example 10).
[0063] In the present invention, the center line average roughness Ra of the surface 7a of the innermost layer 7 is set to 0.05 μm to 1 μm, and more preferably, the center line average roughness Ra of the surface 7a of the innermost layer 7 is set to 0.1 μm to 1 μm. Also, the thickness of the innermost layer 7 is preferably set to 2 μm to 40 μm.
[0064] In the case where the sealant layer 3 has the first intermediate layer 8, it is preferable to use an elastomer-modified olefin-based resin as the resin constituting the first intermediate layer 8. The elastomer-modified olefin-based resin (polypropylene block copolymer) is preferably made of an elastomer-modified homopolypropylene or / and an elastomer-modified random copolymer. The elastomer-modified random copolymer is an elastomer-modified random copolymer containing "propylene" and "other copolymer components other than propylene" as copolymer components, and the "other copolymer components other than propylene" are not particularly limited, but examples thereof include olefin components such as ethylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, and butadiene. The elastomer is not particularly limited, but it is preferable to use an olefin-based thermoplastic elastomer. The olefin-based thermoplastic elastomer is not particularly limited, but examples thereof include EPR (ethylene propylene rubber), propylene-butene elastomer, propylene-butene-ethylene elastomer, EPDM (ethylene-propylene-diene rubber), and the like. Among these, it is preferable to use EPR (ethylene propylene rubber).
[0065] Regarding the elastomer-modified olefin-based resin, the "elastomer-modified" aspect may be a graft polymerization of an elastomer, an addition of an elastomer to an olefin-based resin (homopolypropylene and / or the random copolymer), or another modification aspect.
[0066] In addition, when the sealant layer 3 has a configuration including the first intermediate layer 8, it is preferable that a lubricant is contained in the first intermediate layer 8. Examples of the lubricant include the same lubricants as those exemplified as the lubricant contained in the innermost layer 7. Moreover, it is preferable that the thickness of the first intermediate layer 8 is set to 10 μm to 60 μm.
[0067] In the case where the sealant layer 3 has the second intermediate layer 9, it is preferable to use a random copolymer containing "propylene" and "other copolymer components other than propylene" as copolymer components as the resin constituting the second intermediate layer 9. Regarding the random copolymer, the "other copolymer components other than propylene" are not particularly limited, and examples thereof include olefin components such as ethylene, 1-butene, 1-hexene, 1-pentene, and 4-methyl-1-pentene, as well as butadiene.
[0068] In addition, when the sealant layer 3 has the second intermediate layer 9, it is preferable that the second intermediate layer 9 contains a lubricant. Examples of the lubricant include the same lubricants as those exemplified as the lubricant contained in the innermost layer 7. The thickness of the second intermediate layer 9 is preferably set to 2 μm to 40 μm.
[0069] In the present invention, a heat-resistant resin that does not melt at the heat-sealing temperature when heat-sealing an exterior material is used as the heat-resistant resin constituting the heat-resistant resin layer (outer layer) 2. As the heat-resistant resin, a heat-resistant resin having a melting point 10° C. or more higher than the melting point of the sealant layer 3 is preferably used, and a heat-resistant resin having a melting point 20° C. or more higher than the melting point of the sealant layer 3 is particularly preferably used.
[0070] The heat-resistant resin layer (outer layer) 2 is not particularly limited, but examples thereof include polyamide films such as nylon films, polyester films, etc., and these stretched films are preferably used. Among them, it is particularly preferable to use biaxially stretched polyamide films such as biaxially stretched nylon films, biaxially stretched polybutylene terephthalate (PBT) films, biaxially stretched polyethylene terephthalate (PET) films, or biaxially stretched polyethylene naphthalate (PEN) films as the heat-resistant resin layer 2. The nylon film is not particularly limited, but examples thereof include 6 nylon film, 6,6 nylon film, and MXD nylon film. The heat-resistant resin layer 2 may be formed of a single layer, or may be formed of a multilayer structure consisting of, for example, a polyester film / polyamide film (such as a multilayer structure consisting of a PET film / nylon film). In the case of the multilayer structure, it is preferable to arrange the polyester film side on the outermost side.
[0071] The thickness of the outer layer 2 is preferably 2 μm to 50 μm. When a polyester film is used, the thickness is preferably 5 μm to 40 μm, and when a nylon film is used, the thickness is preferably 15 μm to 50 μm. By setting the thickness to equal to or greater than the above-mentioned preferable lower limit, sufficient strength as an exterior material can be ensured, and by setting the thickness to equal to or less than the above-mentioned preferable upper limit, stress during molding such as stretch molding and drawing molding can be reduced, improving moldability.
[0072] In the present invention, the metal foil layer 4 plays a role of imparting gas barrier properties that prevent the intrusion of oxygen and moisture to the packaging material 1. The metal foil layer 4 is not particularly limited, but examples thereof include aluminum foil, SUS foil (stainless steel foil), copper foil, nickel foil, etc., and among these, it is preferable to use aluminum foil. The thickness of the metal foil layer 4 is preferably 15 μm to 100 μm. By being 15 μm or more, it is possible to prevent the occurrence of pinholes during rolling when manufacturing the metal foil, and by being 100 μm or less, it is possible to reduce stress during molding such as stretch molding and drawing molding, thereby improving formability. Among these, the thickness of the metal foil layer 4 is more preferably 15 μm to 45 μm. In addition, as the aluminum foil, A8079-O material and A8021-O material specified in JIS H4160:2006 are suitable.
[0073] It is preferable that at least the inner surface (the surface on the second adhesive layer 6 side) of the metal foil layer 4 is subjected to a chemical conversion treatment. By performing such a chemical conversion treatment, corrosion of the metal foil surface due to the contents (such as the electrolyte of a battery) can be sufficiently prevented. Examples of such chemical conversion treatments include chromate treatment.
[0074] The first adhesive layer (outer adhesive layer) 5 is not particularly limited, but examples thereof include a polyurethane polyolefin adhesive layer, a polyurethane adhesive layer, a polyester polyurethane adhesive layer, a polyether polyurethane adhesive layer, etc. The thickness of the first adhesive layer 5 is preferably set to 1 μm to 6 μm.
[0075] The second adhesive layer (inner adhesive layer) 6 is not particularly limited, and may be, for example, one of the adhesives exemplified as the first adhesive layer 5, but it is preferable to use a polyolefin adhesive that is less likely to swell with an electrolyte. Among them, it is particularly preferable to use an acid-modified polyolefin adhesive. Examples of the acid-modified polyolefin adhesive include a maleic acid-modified polypropylene adhesive and a fumaric acid-modified polypropylene adhesive. The thickness of the second adhesive layer 6 is preferably set to 1 μm to 5 μm.
[0076] In the present invention, by providing the above-mentioned configuration, the amount of lubricant present (adhered) on the surface 7a of the innermost layer 7 of the sealant layer 3 is 0.1 μg / cm 2 ~0.6μg / cm 2 In particular, the amount of lubricant present on the surface 7a of the innermost layer 7 is preferably in the range of 0.1 μg / cm 2 ~0.3μg / cm 2 It is more preferable that the range is .
[0077] In addition, in the present invention, by providing the above-mentioned configuration, the amount of lubricant present (adhered) on the surface (outer surface) of the outer layer 2 is 0.1 μg / cm 2 ~0.6μg / cm 2 In particular, the amount of lubricant present on the surface of the outer layer 2 is preferably in the range of 0.1 μg / cm 2 ~0.3μg / cm 2 It is more preferable that the range is .
[0078] In the present invention, by having the above-mentioned configuration, it is preferable that the dynamic friction coefficient of the surface 7a of the innermost layer 7 of the sealant layer 3 is 0.3 or less.
[0079] The exterior material 1 for an electricity storage device of the present invention can be molded (deep drawing, stretch molding, etc.) to obtain an exterior case 10 for an electricity storage device (see FIG. 5). The exterior material 1 of the present invention can also be used as it is without being molded (see FIG. 5).
[0080] FIG. 4 shows an embodiment of an electricity storage device 30 constructed using the exterior material 1 of the present invention. This electricity storage device 30 is a lithium ion secondary battery. In this embodiment, as shown in FIGS. 4 and 5, an exterior member 15 is constructed by a case 10 obtained by molding the exterior material 1 and a planar exterior material 1 that was not used for molding. Thus, a substantially rectangular parallelepiped electricity storage device main body (electrochemical element, etc.) 31 is accommodated in the accommodation recess of the exterior case 10 obtained by molding the exterior material 1 of the present invention, and the exterior material 1 of the present invention is placed on the electricity storage device main body 31 with its inner layer 3 side facing inward (lower side) without being molded, and the peripheral portion of the inner layer 3 of the planar exterior material 1 and the inner layer 3 of the flange portion (sealing peripheral portion) 29 of the exterior case 10 are sealed and joined by heat sealing to construct the electricity storage device 30 of the present invention (see FIGS. 4 and 5). The inner surface of the storage recess of the exterior case 10 is an inner layer (sealant layer) 3, and the outer surface of the storage recess is an outer layer (heat-resistant resin layer) 2 (see FIG. 5).
[0081] 4, reference numeral 39 denotes a heat seal portion at which the peripheral portion of the exterior material 1 and a flange portion (sealing peripheral portion) 29 of the exterior case 10 are joined (fused) to each other. In the electricity storage device 30, a tip portion of a tab lead connected to an electricity storage device main body 31 is led out to the outside of the exterior member 15, but is not shown in the figure.
[0082] The electricity storage device main body 31 is not particularly limited, but examples thereof include a battery main body, a capacitor main body, and a condenser main body.
[0083] The width of the heat-sealed portion 39 is preferably set to 0.5 mm or more. By setting the width to 0.5 mm or more, sealing can be performed reliably. In particular, the width of the heat-sealed portion 39 is preferably set to 3 mm to 15 mm.
[0084] In the above embodiment, the exterior member 15 is configured to include an exterior case 10 obtained by molding the exterior material 1 and a planar exterior material 1 (see Figures 4 and 5), but is not limited to such a combination. For example, the exterior member 15 may be configured to include a pair of exterior materials 1, or a pair of exterior cases 10. EXAMPLES
[0085] Next, specific examples of the present invention will be described, but the present invention is not particularly limited to these examples.
[0086] <Example 1> A chemical conversion coating was formed by applying a chemical conversion solution consisting of phosphoric acid, polyacrylic acid (acrylic resin), a chromium (III) salt compound, water, and alcohol to both sides of an aluminum foil 4 having a thickness of 40 μm, and then drying at 180° C. The chromium deposition amount of this chemical conversion coating was 10 mg / m per side. 2 It was.
[0087] Next, a biaxially oriented nylon 6 film 2 having a thickness of 25 μm was dry laminated (attached) to one surface of the aluminum foil 4 that had been subjected to the chemical conversion treatment via a two-liquid curing urethane adhesive 5 .
[0088] Next, a second intermediate layer film (second intermediate layer) 9 having a thickness of 6 μm containing an ethylene-propylene random copolymer and 500 ppm of erucic acid amide, a first intermediate layer film (first intermediate layer) 8 having a thickness of 28 μm containing an elastomer-modified olefin resin (block PP) and 500 ppm of erucic acid amide, and an innermost layer film (innermost layer) 7 having a thickness of 6 μm containing an ethylene-propylene random copolymer, 1.0 mass % of high-density polyethylene resin powder (surface-roughening material), and 500 ppm of erucic acid amide were co-extruded using a T-die so as to laminate the three layers in this order. A sealant film (second intermediate layer film 9 / first intermediate layer film 8 / innermost layer film 7) 3 having a thickness of 40 μm was obtained by laminating three layers from the first intermediate layer film 9 / first intermediate layer film 8 / innermost layer film 7. The second intermediate layer film 9 side of the sealant film 3 was superimposed on the other side of the aluminum foil 4 after the dry lamination via a two-liquid curing type maleic acid modified polypropylene adhesive 6, and the two were dry laminated by being pressed between a rubber nip roll and a laminating roll heated to 100° C., and then aged (heated) at 40° C. for 10 days to obtain an exterior material for an electricity storage device 1 having the configuration shown in FIG. 2. The center line average roughness Ra of the surface 7a of the innermost layer 7 of the sealant layer 3 of the obtained exterior material for an electricity storage device 1 was 0.13 μm.
[0089] The two-component curing maleic acid-modified polypropylene adhesive used was an adhesive solution containing 100 parts by mass of maleic acid-modified polypropylene (melting point 80° C., acid value 10 mgKOH / g) as a base agent, 8 parts by mass of an isocyanurate of hexamethylene diisocyanate (NCO content: 20% by mass) as a curing agent, and a solvent. The adhesive solution was applied at a solid content of 2 g / m 2 The coating was applied to the other surface of the aluminum foil 4 so as to become 90° C., and the coating was dried by heating. After that, the coating was laminated on the surface of the second intermediate layer film 9 of the sealant film 3 .
[0090] The above high-density polyethylene resin (roughened surface material) has a MFR of 0.2 g / 10 min at 190°C and a density of 0.963 g / cm 3, and swell of 40%, and the high density polyethylene resin was produced in a slurry loop process using a Phillips catalyst.
[0091] <Example 2> An exterior material for an electricity storage device 1 having the configuration shown in Figure 2 was obtained in the same manner as in Example 1, except that the content of high-density polyethylene resin (surface-roughening material) in the innermost layer film (innermost layer) 7 was changed from 1.0 mass% to 5.0 mass%.
[0092] <Example 3> An outer casing material 1 for an electricity storage device having the configuration shown in Figure 2 was obtained in the same manner as in Example 2, except that behenic acid amide was used instead of erucic acid amide as the lubricant contained in the second intermediate layer film 9, the first intermediate layer film 8 and the innermost layer film 7.
[0093] <Example 4> An outer casing material for an electricity storage device 1 having the configuration shown in FIG. 2 was obtained in the same manner as in Example 2, except that the content of erucamide in the innermost layer film (innermost layer) 7 was changed from 500 ppm to 1000 ppm.
[0094] <Example 5> An exterior material for an electricity storage device 1 having the configuration shown in Figure 2 was obtained in the same manner as in Example 1, except that the content of high-density polyethylene resin (surface-roughening material) in the innermost layer film (innermost layer) 7 was changed from 1.0 mass% to 10.0 mass%.
[0095] <Example 6> An exterior material for an electricity storage device 1 having the configuration shown in Figure 2 was obtained in the same manner as in Example 1, except that the content of high-density polyethylene resin (surface-roughening material) in the innermost layer film (innermost layer) 7 was changed from 1.0 mass% to 15.0 mass%.
[0096] <Example 7> An exterior material for an electricity storage device 1 having the configuration shown in Figure 2 was obtained in the same manner as in Example 1, except that the content of high-density polyethylene resin (surface-roughening material) in the innermost layer film (innermost layer) 7 was changed from 1.0 mass% to 20.0 mass%.
[0097] <Example 8> An exterior material for an electricity storage device 1 having the configuration shown in Figure 2 was obtained in the same manner as in Example 1, except that the content of high-density polyethylene resin (surface-roughening material) in the innermost layer film (innermost layer) 7 was changed from 1.0 mass% to 30.0 mass%.
[0098] <Example 9> An exterior material for an electricity storage device 1 having the configuration shown in Figure 2 was obtained in the same manner as in Example 1, except that the content of high-density polyethylene resin (surface-roughening material) in the innermost layer film (innermost layer) 7 was changed from 1.0 mass% to 35.0 mass%.
[0099] <Example 10> An outer casing material for an electricity storage device 1 having the configuration shown in FIG. 2 was obtained in the same manner as in Example 3, except that the innermost layer film (innermost layer) 7 further contained 2500 ppm of acrylic beads as an antiblocking agent (AB agent).
[0100] <Example 11> The high-density polyethylene resin (surface-roughening material) contained in the innermost layer film (innermost layer) 7 has an MFR of 0.2 g / 10 min and a density of 0.945 g / cm 3 An outer casing material 1 for an electricity storage device having the configuration shown in Figure 2 was obtained in the same manner as in Example 4, except that a high-density polyethylene resin (roughened surface material) having a swell ratio of 35 and produced by a slurry loop method using a Phillips catalyst was used.
[0101] <Example 12> The high-density polyethylene resin (surface-roughening material) contained in the innermost layer film (innermost layer) 7 has an MFR of 0.2 g / 10 min and a density of 0.955 g / cm 3 An outer casing material 1 for an electricity storage device having the configuration shown in Figure 2 was obtained in the same manner as in Example 5, except that a high-density polyethylene resin (roughened surface material) having a swell ratio of 45 and produced by a slurry loop method using a Phillips catalyst was used.
[0102] <Example 13> The high-density polyethylene resin (surface-roughening material) contained in the innermost layer film (innermost layer) 7 has an MFR of 2 g / 10 min at 190° C. and a density of 0.954 g / cm 3 An exterior material 1 for an electricity storage device having the configuration shown in Figure 2 was obtained in the same manner as in Example 6, except that a high-density polyethylene resin (surface-roughening material) having a swell ratio of 30 and produced by a slurry loop method using a Ziegler catalyst was used.
[0103] <Example 14> The high-density polyethylene resin (surface-roughening material) contained in the innermost layer film (innermost layer) 7 has an MFR of 3 g / 10 min at 190° C. and a density of 0.955 g / cm 3 An exterior material 1 for an electricity storage device having the configuration shown in Figure 2 was obtained in the same manner as in Example 7, except that a high-density polyethylene resin (roughened surface material) having a swell ratio of 20 and produced by a slurry loop method using a Ziegler catalyst was used.
[0104] <Example 15> As a surface roughening material to be contained in the innermost layer film (innermost layer) 7, instead of high-density polyethylene resin, a material having an MFR of 2 g / 10 min at 190 ° C. and a density of 0.921 g / cm 3 An outer casing material 1 for an electricity storage device having the configuration shown in FIG. 2 was obtained in the same manner as in Example 5, except that a low-density polyethylene resin having a swell ratio of 20 and produced in a gas-phase fluidized bed using a Ziegler catalyst was used.
[0105] <Example 16> As a surface roughening material to be contained in the innermost layer film (innermost layer) 7, instead of high-density polyethylene resin, a material having an MFR of 3 g / 10 min at 190 ° C. and a density of 0.915 g / cm 3 An exterior material 1 for an electricity storage device having the configuration shown in Figure 2 was obtained in the same manner as in Example 5, except that a low-density polyethylene resin having a swell ratio of 35 and produced in a high-pressure autoclave using a peroxide catalyst was used.
[0106] <Example 17> As the sealant film, a 32 μm-thick first intermediate layer film (first intermediate layer) 8 containing an elastomer-modified olefin resin (block PP) and 500 ppm of erucamide, and an 8 μm-thick innermost layer film (innermost layer) 7 containing an ethylene-propylene random copolymer, 10.0 mass % high-density polyethylene resin (surface-roughening material), and 500 ppm of erucamide were co-extruded using a T-die to form a 40 μm-thick sealant film (first intermediate layer film 8 / innermost layer film 7) 3 formed by laminating these two layers, and a two-component curing type maleic acid-modified polypropylene adhesive 6 was used to overlap the other side of the dry-laminated aluminum foil 4. An exterior material for an electricity storage device 1 having the configuration shown in FIG. 1 was obtained in the same manner as in Example 1, except that the first intermediate layer film 8 side of this sealant film 3 was overlapped on the other side of the dry-laminated aluminum foil 4 via a two-component curing type maleic acid-modified polypropylene adhesive 6.
[0107] <Example 18> As the sealant film, a 40 μm-thick sealant film (sealant film consisting only of the innermost layer film 7) 3 was used, which was obtained by extruding a composition containing an ethylene-propylene random copolymer, 10.0 mass % high-density polyethylene resin (roughening material), and 500 ppm erucamide using a T-die, and this sealant film 3 was laminated on the other side of the dry-laminated aluminum foil 4 via a two-component curing type maleic acid-modified polypropylene adhesive 6. An exterior material for an electricity storage device 1 having the configuration shown in Figure 3 was obtained in the same manner as in Example 1, except that the sealant film 3 was laminated on the other side of the dry-laminated aluminum foil 4 via a two-component curing type maleic acid-modified polypropylene adhesive 6.
[0108] <Comparative Example 1> An outer casing material for an electricity storage device was obtained in the same manner as in Example 3, except that the innermost layer film (innermost layer) 7 did not contain a surface-roughening material (high-density polyethylene resin).
[0109] <Reference example 1> An exterior material for a storage battery device was obtained in the same manner as in Example 1, except that the erucamide content in the second intermediate layer film (second intermediate layer) 9 was changed from 500 ppm to 1000 ppm, the erucamide content in the first intermediate layer film (first intermediate layer) 8 was changed from 500 ppm to 1000 ppm, and the innermost layer film (innermost layer) 7 was a film containing an ethylene-propylene random copolymer, 1000 ppm of erucamide and 2500 ppm of silica particles (anti-blocking agent).
[0110] <Reference example 2> An outer casing material for an electricity storage device was obtained in the same manner as in Reference Example 1, except that the content of erucamide in the first intermediate layer film (first intermediate layer) 8 was changed from 1000 ppm to 2500 ppm.
[0111] <Reference example 3> An outer casing material for an electricity storage device was obtained in the same manner as in Reference Example 1, except that the content of erucamide in the first intermediate layer film (first intermediate layer) 8 was changed from 1000 ppm to 5000 ppm.
[0112] [Table 1]
[0113] [Table 2]
[0114] [Table 3]
[0115] [Table 4]
[0116] In Examples 1 to 18, Comparative Example 1, and Reference Examples 1 to 3, the elastomer-modified olefin resin comprises an EPR-modified homopolypropylene and an EPR-modified ethylene-propylene random copolymer, where EPR stands for ethylene-propylene rubber.
[0117] In the table, the following abbreviations represent the following resins. "Random PP": Ethylene-propylene random copolymer "Block PP": the above-mentioned elastomer-modified olefin resin (polypropylene block copolymer) "AB agent"...Anti-blocking agent "Philips"...Philips Catalyst "Ziegler"...Ziegler catalyst "Peroxide"...peroxide catalyst “Slurry”: Slurry loop method.
[0118] Each of the exterior materials for an electricity storage device obtained as described above was evaluated based on the following evaluation method. The results are shown in Tables 1 to 4. The dynamic friction coefficients of the innermost layer surface shown in Tables 1 to 4 are dynamic friction coefficients measured for the surface 7a of the innermost layer of each exterior material in accordance with JIS K7125-1995.
[0119] <Method for measuring the centerline average roughness Ra of the surface of the innermost layer of exterior material> In accordance with JIS B0601-2001, the center line average roughness Ra of the surface of the innermost layer of each exterior material for an electricity storage device was measured using "SURFTEST SV600" manufactured by Mitutoyo Corporation.
[0120] <Method for evaluating the amount of lubricant present on the surface of the innermost layer of exterior material> Two rectangular test pieces measuring 100 mm long x 100 mm wide were cut out from each exterior material for power storage devices, and the two test pieces were then overlapped and the periphery of each sealant layer was heat sealed at a heat sealing temperature of 200°C to produce a bag. 1 mL of acetone was injected into the internal space of this bag using a syringe, and the bag was left in a state where the surface 7a of the innermost layer 7 of the sealant layer was in contact with the acetone for 3 minutes, after which the acetone was removed from the bag. The amount of lubricant contained in the removed liquid was measured and analyzed using a gas chromatograph to determine the amount of lubricant (μg / cm) present on the surface of the innermost layer of the exterior material. 2 ) was calculated. 2 The amount of lubricant per unit was determined.
[0121] <Method for evaluating the amount of lubricant present on the surface of the outer layer of exterior materials> The amount of lubricant (μg / cm) present on the surface of the outer layer of the packaging material was measured in the same manner as in the above "Method for evaluating the amount of lubricant present on the surface of the innermost layer," except that the bag was prepared so that the outer layer was on the inside of the bag and the surface of the outer layer was brought into contact with acetone. 2 ) was calculated. That is, the surface area of the outer layer was 2 The amount of lubricant per unit was determined.
[0122] <Moldability evaluation method> A single-stage deep drawing process was performed on the exterior material using a depth-free straight mold under the following molding conditions, and the moldability was evaluated for each molding depth (9mm, 8mm, 7mm, 6mm, 5mm, 4mm, 3mm, 2mm), and the maximum molding depth (mm) at which good molding without any pinholes at the corners could be performed was investigated. The maximum molding depth of 6mm or more was judged as "◎", the maximum molding depth of 4mm or more but less than 6mm was judged as "○", and the maximum molding depth of less than 4mm was judged as "×". The presence or absence of pinholes was checked by visually observing the presence or absence of transmitted light passing through the pinholes. (Molding conditions) Mold: Punch: 33.3mm x 53.9mm, Die: 80mm x 120mm, Corner R: 2mm, Punch R: 1.3mm, Die R: 1mm Wrinkle holding pressure: Gauge pressure: 0.475MPa, Actual pressure (calculated value): 0.7MPa Material: SC (carbon steel), punch R only chrome plated.
[0123] <Method for assessing the presence or absence of white powder> After cutting out a rectangular test piece of 600 mm long x 100 mm wide from each exterior material for electric storage devices, the obtained test piece was placed on a test stand with the inner sealant layer 3 side (i.e., the surface 7a of the innermost layer) facing up, and a SUS weight (mass 1.3 kg, contact surface size 55 mm x 50 mm) with a black cloth wrapped around it and a black surface was placed on the upper surface of the test piece, and the weight was pulled in a horizontal direction parallel to the upper surface of the test piece at a pulling speed of 4 cm / sec, so that the weight was pulled over a length of 400 mm in contact with the upper surface of the test piece. The cloth (black) on the contact surface of the weight after the pulling movement was visually observed, and a case in which white powder was noticeably generated on the surface of the cloth (black) was marked as "x", a case in which only a small amount of white powder was generated was marked as "△", and a case in which there was almost no white powder or no white powder was observed was marked as "○". The black cloth used was "Static Electricity Removal Sheet S SD2525 3100" manufactured by TRUSCO.
[0124] <Method for evaluating the presence or absence of whitening during molding> Using a deep drawing tool manufactured by Amada Co., Ltd., the exterior material was deep drawn into a rectangular shape with a depth of 5 mm under the following molding conditions, and the inner surface of the accommodation recess of the obtained molded body (three sides of the sealant layer) was visually observed, and the presence or absence and the degree of whitening were evaluated based on the following judgment criteria. (Judgment criteria) The molded bodies after molding were visually observed, and those with no or almost no whitening were marked with "◎", those with little whitening were marked with "◯", those with some whitening were marked with "△", and those with significant whitening were marked with "X". (Molding conditions) Mold: Punch: 33.3mm x 53.9mm, Die: 80mm x 120mm, Corner R: 2mm, Punch R: 1.3mm, Die R: 1mm Wrinkle holding pressure: Gauge pressure: 0.475MPa, Actual pressure (calculated value): 0.7MPa Material: SC (carbon steel), punch R only chrome plated.
[0125] As is clear from the table, the exterior packaging materials for an electricity storage device of Examples 1 to 18 of the present invention have excellent moldability, are less likely to produce white powder on the surface of the exterior packaging material, and are also less likely to whiten during molding.
[0126] In contrast, Comparative Example 1, which does not contain a surface-roughening material, was poor in moldability. In addition, in order to obtain a good evaluation with a configuration that does not contain a surface-roughening material, it is necessary to increase the lubricant content in the sealant layer as in Reference Examples 1 to 3 and to contain a large content of antiblocking agent (AB agent) in the innermost layer. In this way, when the innermost layer contains a large amount of antiblocking agent, the antiblocking agent is pushed into the inside when the exterior material is wound up, which tends to reduce the slipperiness and the antiblocking agent is likely to fall off. In Reference Example 3, which has the highest lubricant content in the sealant layer, white powder was prominently displayed on the surface of the exterior material. [Industrial Applicability]
[0127] Specific examples of the electrical storage device packaging material produced using the sealant film according to the present invention and the electrical storage device packaging material according to the present invention include, for example, ·Electricity storage devices such as lithium secondary batteries (lithium ion batteries, lithium polymer batteries, etc.) ·Lithium ion capacitors Electric double layer capacitor ·All-solid-state battery The electric storage device according to the present invention is used as an exterior material for various electric storage devices such as those exemplified above. [Explanation of symbols]
[0128] 1. Exterior materials for power storage devices 2...Heat-resistant resin layer (outer layer) 3...Sealant layer (inner layer) 4…Metal foil layer 5…Second adhesive layer (outer adhesive layer) 6...First adhesive layer (inner adhesive layer) 7…Innermost layer 7a…Surface of the innermost layer of the sealant layer 8…First middle class 9. The second middle class 10...Outer case for power storage device (molded body) 15…Exterior material 30…Electricity storage device 31...Electricity storage device main body
Claims
1. An exterior material for an electricity storage device, comprising a heat-resistant resin layer as an outer layer, a sealant layer as an inner layer, and a metal foil layer disposed between these layers, The sealant layer is composed of one or more layers, and the innermost layer of the sealant layer contains a random copolymer containing propylene and other copolymer components other than propylene as copolymer components, a surface-roughening material, and a lubricant; The surface roughening material is made of particles containing a thermoplastic resin, The center line average roughness Ra of the surface of the innermost layer is 0.05 μm to 1 μm, The difference between the melt density of the random copolymer containing propylene and other copolymer components other than propylene as copolymer components and the melt density of the surface-roughening material is 0.3 g / cm 3 An exterior material for an electricity storage device, characterized in that:
2. 2. The exterior material for an electricity storage device according to claim 1, wherein the thermoplastic resin constituting the surface-roughening material is a polyethylene resin.
3. 3. The electrical storage device packaging material according to claim 1, wherein the content of the surface roughening material in the innermost layer of the sealant layer is 1% by mass to 30% by mass, and the content of the lubricant in the innermost layer is more than 0 ppm and not more than 1000 ppm.
4. The exterior packaging material for an electricity storage device according to any one of claims 1 to 3, wherein the sealant layer is made up of a plurality of layers.
5. the sealant layer includes the innermost layer and a first intermediate layer laminated on a surface of the innermost layer on the metal foil layer side, The first intermediate layer contains an elastomer-modified olefin-based resin, The elastomer-modified olefin-based resin comprises an elastomer-modified homopolypropylene and / or an elastomer-modified random copolymer, The exterior material for an electricity storage device according to claim 4 , wherein the elastomer-modified random copolymer is an elastomer-modified product of a random copolymer containing propylene and a copolymer component other than propylene as a copolymer component.
6. the sealant layer includes the innermost layer, a first intermediate layer laminated on a surface of the innermost layer facing the metal foil layer, and a second intermediate layer laminated on a surface of the first intermediate layer facing the metal foil layer, The first intermediate layer contains an elastomer-modified olefin-based resin, The elastomer-modified olefin-based resin comprises an elastomer-modified homopolypropylene and / or an elastomer-modified random copolymer, The elastomer-modified random copolymer is an elastomer-modified random copolymer containing propylene and other copolymer components other than propylene as copolymer components, The packaging material for an electricity storage device according to claim 4 , wherein the second intermediate layer contains a random copolymer containing, as a copolymerization component, propylene and a copolymerization component other than propylene.
7. An exterior case for an electricity storage device, comprising a molded article of the exterior material for an electricity storage device according to any one of claims 1 to 6.
8. A main body of the electricity storage device; An exterior member comprising the exterior material for an electricity storage device according to any one of claims 1 to 6 and / or the exterior case for an electricity storage device according to claim 7, The power storage device, wherein the power storage device main body is exteriorly covered with the exterior member.
Citation Information
Patent Citations
Multilayered laminate
JP1995125160A
Polypropylene-based single-layer film
JP2003064194A
Laminated material for secondary battery container and secondary battery container
JP2003288865A
Packing material for battery
JP2006318685A
External facing material for secondary battery and secondary battery
JP2013101764A